Pengaruh Modifikasi Burner dan Variasi Campuran Bahan Bakar Pirolisis Limbah Polipropilena terhadap Efisiensi Termal dan Karakteristik Pembakaran - Aditya Wahyu Pratama; Novangga Adi Mulyono; Audha Fitrah Aulina; Reynaldi Akbar Ali; Faruq Avero Azhar; Andik Irawan (Jurnal Teknik Terapan, 2026)
This study presents the optimization of burner design and experimental evaluation using liquid fuel derived from polypropylene (PP) waste pyrolysis to achieve high thermal efficiency. The increasing accumulation of plastic waste and rising energy demand have driven the development of alternative fuels and more efficient combustion systems. In this work, polypropylene waste was converted into liquid fuel through a pyrolysis process and subsequently utilized as the primary fuel in a modified burner system. The optimization focused on key design parameters, including nozzle diameter, air–fuel mixing configuration, and combustion chamber geometry to enhance atomization quality, flame stability, and heat transfer performance.Experimental tests were conducted under various operating conditions to evaluate combustion characteristics, fuel consumption rate, flame temperature, and thermal efficiency. The results show that the optimized burner configuration produced a stable blue–orange flame with improved atomization and more complete combustion compared to the initial design. The maximum thermal efficiency achieved was 105.54%, indicating a significant improvement due to better air–fuel mixing and reduced heat losses during the combustion process. Furthermore, the pyrolysis oil demonstrated strong potential as an alternative liquid fuel for small-scale thermal applications.This study provides a practical contribution to waste-to-energy technology by integrating burner design optimization with plastic waste-derived fuel utilization, offering an effective approach to enhance thermal system performance while supporting sustainable and scalable small-scale energy solutions.